Nanosized water treatment residuals improve water retention and phytoavailability of P and Al in biosolids-amended soil. (11th July 2020) - Mahdy, Ahmed; Elkhatib, Elsayed; Sherif, Fatma; Fathi, Nieven; Folaa, Maha
Abstract: Two lysimeter experiments were conducted to evaluate the impacts of biosolids and drinking water treatment residual nanoparticles (nWTRs) on phosphorus and aluminum phytoavailability and yield of corn plants. Two consecutive experiments were conducted with different application rates of biosolids (0% and 3%) and nWTRs (0%, 0.1%, 0.2%, and 0.3%). The results revealed that the total biomass production (grain plus stover) increased significantly ( p < .05) as a result of nWTRs application at 0.1% rate. Application of nWTRs to biosolids-treated soil slightly decreased yield at 0.2% and 0.3% application rates. The best combination ratio between nWTRs and biosolids at which high corn yield is 0.1% nWTRs to 3% biosolids. Application of 3% biosolids significantly increased bioavailable P in the studied soil, but application of 0.3% nWTRs significantly decreased the bioavailable P concentrations in soil in the two seasons of cultivation. Application of nWTRs at 0.1% and 0.2% rates decreased soil pH in the soil treated with 3% biosolids in first and second seasons of cultivation in comparison with control treatment. The application of nWTRs greatly and significantly ( p < .05) increased the water-holding capacity of studied soil treated with and without biosolids.